Improving reading skills in the english language using storyline online website - Nieto Arcos, Yereling Vickelly (Machala: Universidad Técnica de Machala, 2022)
The purpose of this project is to improve the reading skills in the English language in the students of 3rd grade of General Unified High School, parallel F of the Educational Unit Carmen Mora de Encalada, through technological didactic resources, Although currently didactic methods have been implemented to teach and learn, the habit of reading either in the mother tongue is difficult and it becomes really hard to practice it in a foreign language, that is why with the support of the Storyline Online website we intend to progress in the mastery of this skill. The research has as object of study the teaching-learning process in high school, supported by a qualitative paradigm, within the methods of the theoretical level, the historical-logical, the synthetic analytical and systemic, using techniques at the empirical level, participant observation and a semi-structured interview that will help to demonstrate the before and after process.
El presente proyecto tiene como finalidad el mejoramiento de las habilidades lectoras en el idioma inglés en los alumnos de 3ro de Bachillerato General Unificado, paralelo F de la Unidad Educativa Carmen Mora de Encalada, a través de los recursos didácticos tecnológicos, que aunque en la actualidad se hayan implementado métodos didácticos para enseñar y aprender, el habito de la lectura ya sea en el idioma materno es difícil y se convierte realmente trabajoso practicarlo en un idioma extranjero, es por eso que con el apoyo del sitio web Storyline Online se pretende progresar en el dominio de esta habilidad. La investigación tiene como objeto de estudio el proceso de enseñanza aprendizaje en el bachillerato, apoyada por un paradigma cualitativo, dentro de los métodos del nivel teórico, el histórico-lógico, el analítico sintético y el sistémico, utilizando técnicas a nivel empírico, la observación participante y una entrevista semiestructurada que ayudarán a evidenciar el antes y después del proceso.
Keywords: DIDACTIC TECHNOLOGICAL; STORYLINE ONLINE; READING SKILL AND BACCALAUREATE